Os pescadores e a colônia de pescadores Z-7 de Tocantinópolis: a prática da pesca e os “saberes” populares - Lucas, Wagna Lindemberg Costa (Universidade Federal do Tocantins, 2025)
The fishing culture has been present in the daily lives of riverside dwellers who have lived on the banks of the Tocantins River for generations, as well as in the old (Boa Vista do Pe. João) historic city, the current Tocantinópolis, in the North of Tocantins. We have observed through this that there is generationality in relation to the population that lives on the banks of the Tocantins. The general objective of this research was to understand and analyze the teaching and learning relationships between fishermen and women of the Z-7 Colony of Tocantinópolis. The methodology adopted in this qualitative research is thematic oral history, with interviews with fishermen and women associated with the Z-7 Colony, in order to hear their stories. Through the final analysis of the results of the data collection, documentary research and interviews, it was possible to demonstrate that there is a very strong relationship between the fishermen and the river, as well as a teaching-learning relationship in the fishing culture, with regard to the production and teaching/learning in the production of materials and methods of artisanal fishing. Notably, there is a difference demonstrated here between this type of fishing and professional and sport fishing. Likewise, it was found that both men and women practice fishing, pass on knowledge among themselves and join together and organize themselves into groups and entities in order to demand rights, such as “closed season insurance” and retirement. It is necessary to highlight the relevance and performance of the Z-7 Fishermen’s Colony as an institution representing fishermen, as well as its relevance and fundamental role in dealing with environmental problems and riverine fishermen caused by the construction of the Estreito hydroelectric plant (UHE).